Government‐led e‐commerce expansion project and rural household income: Evidence and mechanisms. - Chen, Shiyi; Liu, Wanlin; Song, Hong; Zhang, Qing (Economic Inquiry, 2024)
This paper examines the impacts of a government‐led e‐commerce expansion project on household income. We find that the project has led to increases in rural household income. The positive impacts are more prominent for lower‐income rural households. The income‐increasing effects are driven by the reduction in information search costs and transportation costs. The provision of complementary interventions for e‐commerce, such as promoting the internet‐related skills of farmers and the expansion of formal financial credit support is also important for the program's success. The results provide policy implications for the design and implementation of government‐led e‐commerce policies in developing economies.